Optimalisasi Peran Masyarakat dalam Pelaksanaan Program Pencegahan dan Penurunan Stunting di Desa Labuhan Bajo Kecamatan Utan, Kabupaten Sumbawa - Has’ad Rahman Attamimi; Yunita Lestari; Hajerah Hajerah (Lembaga Pengembangan Kinerja Dosen, 2025)
A number of regions in Indonesia still have a fairly high percentage of stunting cases, including NTB being one of the 5 provinces with the highest percentage of stunting cases in Indonesia in 2022. Since 2019 until now, Labuhan Bajo Village, Utan District in Sumbawa Regency has been one of The stunting locus village in NTB province has a long record as a stunting locus area. The results of the Stunting Case Audit Evaluation Meeting Phase I in 2024, the Sumbawa Regency Stunting Acceleration Handling Team, led by the Regional Secretary of Sumbawa Regency, stated that there are at least around 200 families in Utan District at risk of stunting. These include prospective brides (catin), young women, pregnant women, postpartum mothers and others. Such conditions are of course not only the responsibility of the government, but more broadly, the community should also be part of the group responsible for the conditions that occur. Therefore, the role of the community in ensuring stunting prevention and reduction programs must be truly ensured. This service is carried out with the aim of optimizing the role of the community in implementing stunting prevention and reduction programs. This service is carried out using counseling methods and discussions with the community to enlighten the community about the importance of preventing and handling stunting. It is hoped that the results of this activity will make the community more aware of the risks and incidents of stunting, that stunting incidents can be reduced or even eliminated.